2010
DOI: 10.1111/j.1600-0528.2009.00501.x
|View full text |Cite
|
Sign up to set email alerts
|

Actuarial life‐table analysis of lower impacted wisdom teeth in general dental practice

Abstract: The study indicates that older patients are less likely to develop the symptoms studied. In addition the authors believe that there is evidence to suggest that general dental practitioners might not be following current guidelines when deciding whether or not to extract an impacted lower third molar in the centres studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 20 publications
2
44
0
Order By: Relevance
“…36 However, most third molars will erupt without symptoms. 7,8 In addition, third molar removal is associated with morbidity, such as pain, swelling, bleeding, infection, and paresthesia; the overall rate of complications varies from 4.6% 9 to 21%. 4 Thus, recommendations to retain and monitor asymptomatic third molars may be considered an appropriate strategy.…”
mentioning
confidence: 99%
“…36 However, most third molars will erupt without symptoms. 7,8 In addition, third molar removal is associated with morbidity, such as pain, swelling, bleeding, infection, and paresthesia; the overall rate of complications varies from 4.6% 9 to 21%. 4 Thus, recommendations to retain and monitor asymptomatic third molars may be considered an appropriate strategy.…”
mentioning
confidence: 99%
“…The study showed that 3% of previously asymptomatic third molars were removed every year, with more wisdom teeth being removed as the patient age increased. In contrast, there was a significant, inverse association between the development of symptoms and age 36 ; thus, older patients were less likely to develop signs/ symptoms that warranted removal. A reviewer for this study highlighted the role of practitioners in discussing the risks and benefits of both retention and removal of asymptomatic lower wisdom teeth with even a slight risk of future loss 37 .…”
Section: Discussionmentioning
confidence: 85%
“…[20][21][22][23] As a precautionary measure, it is a wise advice from medical experts to be prepared for any dental emergency for such a special category of patients. [24][25][26] On the other hand, other group of experts suggests retaining the asymptomatic tooth on the request of patients. This raises a concern over conserving an impacted tooth?…”
Section: Resultsmentioning
confidence: 99%